Local anaesthesia versus spinal anaesthesia in inguinal hernia repair: A systematic review and meta-analysis. Issue 1 (February 2017) - Prakash, Deepali; Heskin, Leonie; Doherty, Sally; Galvin, Rose
Abstract: Background: Inguinal hernias are a significant cause of morbidity. The purpose of this systematic review and meta-analysis is to determine the totality of evidence regarding the effectiveness of local anaesthesia when compared to spinal anaesthesia in individuals undergoing open inguinal hernia repair. Methods: A systematic literature search was conducted. Inclusion criteria were randomised controlled trials (RCTs) comparing spinal and local anaesthesia on clinical and self-reported outcomes, in patients undergoing open inguinal hernia repairs. The methodological quality was assessed using the Cochrane risk of bias tool. The mode of analysis used was the difference in outcomes between the groups post-surgery and at follow-up time points. Statistical heterogeneity was assessed using the I 2 statistic. Results: Ten original RCTs were included, with a total of 1379 patients. There was no significant difference in operative time between the groups [Random Effects Model, MD −0.70 min (95% CI, −5.80 to 4.40 min), p  = 0.79, I 2  = 84%]. Patients in the local anaesthetic group experienced significantly less pain than those in the spinal group [Fixed Effects Model, SMD −0.63 (95% CI, −0.81 to −0.46), p  < 0.01, I 2  = 49%], lower rates of urinary retention [FEM, RR 0.03 (95% CI 0.01–0.08), p  < 0.01, I 2  = 0%], decreased rates of anaesthetic failure [FEM, OR 0.17 (95% CI 0.06–0.45), p  < 0.01, I 2  = 0%], and increased satisfaction with the anaesthetic [FEM, OR 3.40 (95% CI 2.09–5.52), p  < 0.01, I 2  = 0%]. The methodological quality of studies was variable. Conclusion: Our findings support the use of local anaesthetic in adult patients undergoing open repair for a primary inguinal hernia.